Magnetic resonance spectroscopic comparison of the effects of resveratrol (3,4',5-trihydroxy stilbene) to conjugated equine estrogen, tibolone and raloxifene on ovariectomized rat brains - Celik, O; Erdem, G; Hascalik, S; Karakas, HM; Tamser, M (Elsevier Science Bv, 2005)
Objective: To investigate the effects of resveratrol on basic cerebral metabolites of in the brains of ovariectomized rats. Materials and methods: Twenty-four bilaterally ovariectomized rats were randomly assigned into six groups With four rats in each group. The groups consisted of sham-operated (control), ovariectomized, resveratrol, conjugated equine estrogen (CEE), tibolone and raloxifene treated rats. Drug administration started at the 5th day following ovariectomy and continued for 35 days. At the end of the entire Course, in vivo single vowel magnetic resonance spectroscopy was performed on whole brains to determine choline, creatine and N-acetyl aspartate (NAA) concentrations. Results: Compared to sham-operated group, ovariectomized group had significantly lower NAA (P < 0.008) but significantly higher choline levels (P < 0.031). Administration of CEE and resveratrol resulted in NAA levels that were similar to those in the sham-operated group, showing that the NAA decrease due to ovariectomy was prevented. Treatment with tibolone and raloxifene resulted in a smaller increase in NAA and the effect failed to reach significance. Administration of resveratrol, CEE, tibolone and raloxifene resulted in choline levels similar to those in sham-operated group, showing that the increase in the ovariectomy group was prevented. Conclusion: Resveratrol causes levels of cerebral metabolites that is similar to conventional hormone replacement agents. This finding may suggest that neuronal function in the postmenopausal state was preserved. More detailed investigation of this issue should be the task of future research. (c) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: resveratrol; magnetic resonance spectroscopy; oopherectomy; rat brain